Hip thrust-based PAP effects on sprint performance of soccer players: heavy-loaded versus optimum-power development protocols - Dello Lacono, A.; Seitz, L. B. (Journal of Sports Sciences, 2019)
This study aimed to investigate the acute effects of two barbell hip thrust-based post-activation potentiation (PAP) protocols on subsequent sprint performance. Using a crossover design, eighteen soccer athletes performed 5 m, 10 m, and 20 m sprints before and 15 s, 4 min, and 8 min after two PAP protocols. The PAP conditioning activities consisted of hip thrust exercises loaded with either 85% 1RM or a load for optimum power development. The resulting 5 m and 10 m sprint performances were impaired at 15 s following both protocols. At 4 min and 8 min, meaningful improvements were observed for the three sprint distances following both of the protocols. Meaningful differences were found when comparing the two PAPs over time: greater impairments in 5 m and 10 m following the 85% of 1 RM protocol after 15 s, and greater improvements in all sprint distances after 4 min and 8 min following the optimum power development protocol. Positive correlations between the hip thrust's 1RM and power values and the overall individual PAP responses were found. This investigation showed that both heavy-loaded and optimum-power hip thrust exercises can induce a PAP response, with the optimum-power development protocol preferred due its higher efficiency.